The meaning of an oath. The Chinese and the Pacific War - Zapata, Antonio (2023)
This article aims to analyze the political conduct of the Peruvian Chinese during the Pacific War. We will delve into the process of incorporating a Chinese unit into the Chilean army as an auxiliary force and its oath on the eve of the battles for the Peruvian capital in January 1881. The sources consist of eyewitness accounts of the ceremony, all of whom were Westerners: Chilean officers, journalists, and some European military observers. Early accounts of the Pacific War from Chilean and Peruvian authors, specifically Vicuña Mackenna and Paz Soldán, respectively, will also be utilized. Finally, we will analyze 19th-century Chinese newspapers containing letters from the coolies discussing their situation in Peru and the war with Chile. The research findings are as follows: The rite was 100% Chinese. It was not related to Chilean or Peruvian patriotic identity but rather to the imminence of a battle. The warrior culture of the coolies was based on the clan wars occurring in Canton between the locals known as Punti and the visitors known as Hakka. The Pacific War presented an opportunity for a large-scale coolie rebellion, leading to severe inter-ethnic clashes in Peru. In letters sent to Chinese newspapers at the time, the coolies provided testimonies recounting their great suffering in Peru, linking the likely Peruvian defeat to the lack of public morality. While defining their status as neutrals, the coolies questioned the motives of Peruvians for looting their businesses. Peruvian historiography acknowledges that the Chinese were acting in self-defense. Except for a small group, they did not align themselves with Chile. In contrast, the vast majority behaved similarly to the other neutrals involved in this international conflict.